2018
DOI: 10.1111/pedi.12665
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 receptor α-chain haplotypes differentially affect soluble IL-7 receptor and IL-7 serum concentrations in children with type 1 diabetes

Abstract: Children with T1D carrying autoimmunity risk- or protection-associated IL7RA haplotypes had both lower sIL-7R serum concentrations as compared to the reference haplotype, but only T1D children with the protective haplotype had lower IL-7 serum levels. Our results suggest additional functional mechanisms of autoimmunity-associated IL7RA variants independent from sIL-7R mediated regulation of IL-7 availability for T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…* Borilova Linhartova P. et al, 2018 [9] CP does not influence the circulating IL-8 levels. Patients with T1DM+CP had higher circulating IL-8 levels than healthy controls+P/non-P. Seyfarth J. et al, 2018 [32] Only T1DM children with the protective haplotype had lower IL-7 serum levels. Al-Lahham Y. et al, 2017 [33] IL-18 rs187238 was not associated with T1DM in a Euro-Brazilian population.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…* Borilova Linhartova P. et al, 2018 [9] CP does not influence the circulating IL-8 levels. Patients with T1DM+CP had higher circulating IL-8 levels than healthy controls+P/non-P. Seyfarth J. et al, 2018 [32] Only T1DM children with the protective haplotype had lower IL-7 serum levels. Al-Lahham Y. et al, 2017 [33] IL-18 rs187238 was not associated with T1DM in a Euro-Brazilian population.…”
Section: Discussionmentioning
confidence: 97%
“…SNPs for IL-7 in T1DM patients were investigated in several valuable works [14,20,31,32]. Hoffman M. et al [14] revealed higher sIL-7R serum concentrations at T1DM onset and decreasing levels during therapy, whereas IL-7 was only higher in long-term patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum of study participants was stored at −80°C for concomitant IL-7 measurement at the University Childrens Hospital in Duesseldorf. Serum IL-7 concentrations were measured as described previously [16,20]. In brief, we used a commercially available highly sensitive ELISA (Human IL-7 Quantikine HS ELISA kit, R&D Systems) according to manufacturer's instructions.…”
Section: Serum Il-7 Measurementmentioning
confidence: 99%
“…The rs6897932 T-allele is associated with protection against autoimmune diseases and causes diminished sIL-7R expression [5]. As a consequence, protective allele carriers generally have lower sIL-7R serum levels with potential effects on sIL-7R reservoir function and IL-7 availability [8,9]. We have previously found using cell lines that the rs6897932 Tallele also affected membrane IL-7R (mIL-7R) expression [10]; however, differences of mIL-7R expression on adaptive immune cell subsets between different IL7RA allele carriers were not found [11].…”
Section: Introductionmentioning
confidence: 99%